(untitled) (Research, Society and Development, 2022)
Objective: To describe the experience of nursing students during the internship in risk classification in the context of urgency and emergency, aiming at the role of nurses in this process. Methodology: This is a descriptive study, of the experience report type, which took place during the students experience in a public emergency and reference hospital in the state of Pará, during the second half of 2021. Results: During the hospital internship period, it was possible to follow the patient’s passage step by step, from his arrival, his reception, classification and referral to the ward, there was the opportunity to use the Manchester Protocol, something that in practice had never been accomplished. In addition to having contact with the patient, solving doubts and also calming them down, performing the classification also in the institution’s system and having safety and autonomy in the conducts. The internship was fundamental for the students, new experiences, domains and autonomy in procedures were acquired, as was passed on from the preceptor to the students, following the role of the nurse in that context. Conclusion: During the curricular internship days in the risk classification, the importance of a nurse trained in the classification was evident, as it is necessary to be cautious in their decisions, it is necessary to be sure about the protocol and to know the exact classification according to the event with the patient, knowing how to manage the environment, in addition to collecting all the information from the patient’s history and forwarding to the ward.